Unveiling Fisheries Supply Chain Performance with SCOR: Challenges for Food Security amid Climate Change - Iskandar, Yelita Anggiane; Vikaliana, Resista; Situmeang, Echa Ratu Prety Claudia; Layman, Pauline Nancy Desline (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
Indonesia’s capture fisheries sector plays a critical role in sustaining coastal livelihoods and national food security; however, production from both aquaculture and capture fisheries has not shown stability nor met the targets of the KKP Strategic Plan (RENSTRA) 2020-2024. In Fisheries Management Area (WPP) 713, particularly Teluk Aru, South Kalimantan, fish catch volumes have been declining, driven by the dual pressures of climate change and inefficiencies in fishing practices, storage, and supply chain management. These challenges not only threaten the availability of fish as a key protein source but also undermine economic growth and community resilience. This study seeks to evaluate the performance of the fisheries supply chain in Teluk Aru by designing indicators that explicitly incorporate climate change adaptation and food security dimensions, which remain underexplored in prior research. Data were collected through surveys, observations, and Focus Group Discussions (FGDs) with fishers, collectors, consumers, and local stakeholders, and analyzed using the Analytic Hierarchy Process (AHP) within the Supply Chain Operations Reference (SCOR) framework. The results identified 17 valid and relevant key performance indicators (KPIs), yielding an overall performance score of 43.71 out of 81.00, categorized as “low.” With only one KPI meeting its target, the findings underscore the urgent need for policy action and supply chain improvements to enhance resilience and sustainability in the fisheries sector.